The Metabolic and Neurochemical Etiopathology of Passive Exposition to Alcohol Consumers - Lamothe, Nery; Lamothe, Mara; Lamothe, Daniel; Villanueva, Ernesto; Bueno, Pilar; Alonso-Altamirano, Alejandro; Clemente-Herrera, Adriana; Hernández, Estuardo; Guillermo Castillo-Vázquez, Francisco; Gerardo Roche, Andrės (Journal of Public Health International, 2021)
A narrative review considers metabolic and neurochemical pathways implicated in passive exposure to alcohol consumers, discussing health effects and research needs.
Keywords: Metabolic; Neurochemical Pathways; Passive Exposure; Alcohol Consumers; Health Effects